Dysregulated nitric oxide signaling as a candidate mechanism of fragile X syndrome and other neuropsychiatric disorders - Colvin, Steven M.; Kwan, Kenneth Y. (Frontiers in Genetics, 2014)
A mechanistic understanding of the pathophysiology underpinning psychiatric disorders is essential for the development of targeted molecular therapies. For fragile X syndrome (FXS), recent mechanistic studies have been focused on the metabotropic glutamate receptor (mGluR) signaling pathway. This line of research has led to the discovery of promising candidate drugs currently undergoing various phases of clinical trial, and represents a model of how biological insights can inform therapeutic strategies in neurodevelopmental disorders. Although mGluR signaling is a key mechanism at which targeted treatments can be directed, it is likely to be one of many mechanisms contributing to FXS. A more complete understanding of the molecular and neural underpinnings of the disorder is expected to inform additional therapeutic strategies. Alterations in the assembly of neural circuits in the neocortex have been recently implicated in genetic studies of autism and schizophrenia, and may also contribute to FXS. In this review, we explore dysregulated nitric oxide signaling in the developing neocortex as a novel candidate mechanism of FXS. This possibility stems from our previous work demonstrating that neuronal nitric oxide synthase 1 (NOS1 or nNOS) is regulated by the FXS protein FMRP in the mid-fetal human neocortex. Remarkably, in the mid-late fetal and early postnatal neocortex of human FXS patients, NOS1 expression is severely diminished. Given the role of nitric oxide in diverse neural processes, including synaptic development and plasticity, the loss of NOS1 in FXS may contribute to the etiology of the disorder. Here, we outline the genetic and neurobiological data that implicate neocortical dysfunction in FXS, review the evidence supporting dysregulated nitric oxide signaling in the developing FXS neocortex and its contribution to the disorder, and discuss the implications for targeting nitric oxide signaling in the treatment of FXS and other psychiatric illnesses.